الضريبة على أرباح الشركات - أمنة, عماري; إيمان, حميداتو; الطيب, هبيته (جامعة الوادي - University of Eloued, 2023)
"بعد التطرق إلى مختلف جوانب الضریبة على أرباح الشركات وكیفیة فرضها وتحصیلها من خلال القیام بدراسة میدانیة وفق ما جاء به المشرع آثر اصلاحاته المتعاقبة على النظام الضریبي عامة وھذا النوع من الضرائب خاصة. خلصنا إلى القول بأن أي فرض لأي ضریبة مهما كان نوعها یستدعي وضع الشروط الضروریة لإزالة أو تخفیف تلك المشاكل المتعلقة بتطبیقها حقا ولا یتسنى ذلك إلا إذا كانت ھذه الشروط متناسبة ودرجة النمو الاقتصادي للبلد. أما بالنسبة للجزائر فما یمكن قوله إن اعتمادھا من ھذا النوع من الضرائب جاء في إطار سعیها نحو إیجاد ضریبة تتسم بالمرونة والسهولة في التطبیق" "After addressing the various aspects of the tax on corporate profits and how to impose and collect it through conducting a field study according to what the legislator stated, the impact of his successive reforms on the tax system in general and this type of tax in particular. We concluded by saying that any imposition of any tax of any kind necessitates the development of the necessary conditions to remove or mitigate those problems related to its real application, and this is only possible if these conditions are commensurate with the degree of economic growth of the country. As for Algeria, what can be said is that its adoption of this type of tax came within the framework of its endeavor to find a tax that is flexible and easy to apply."
Keywords: الضريبة على الارباح; the tax on corporate